Strategi Pengelolaan Limbah Kayu di Kawasan Pantai Mustika Pestanggaran Kabupaten Banyuwangi - Ratna Mustika Yasi; Dwi Gita Anggagana; Rizky Ramadani (Fakultas Teknik, Universitas PGRI Banyuwangi, 2023)
One of the problems in coastal or coastal areas is waste management. Waste can cause environmental problems if its presence is not handled properly. The aim of this activity is to provide direct training, especially in processing wood waste on the coast of Mustika, Pancer hamlet, Pesanggaran subdistrict. This activity includes the observation stage, implementation which consists of socialization and direct training, the final stage is making activity reports and evaluation Waste in the form of wood waste produced in coastal areas is in the form of tree branches carried by currents or branches from trees around the beach. The activity started with observations to see the problem of wood waste accumulation that was not managed properly. The socialization activity on managing wood waste into briquettes was carried out in one day, attended by 30 participants from various levels of society. Based on the analysis, it was found that socialization and training activities in managing Mustika beach wood waste into briquettes are one solution for dealing with the accumulation of rubbish/wood waste in the beach environment that can be implemented by UMKM in the environment around Mustika Beach in the Pesanggaran area.